Analisis dan Optimasi 3D Print Material Carbon Fiber Pla Menggunakan Metode Taguchi-Gra - Hafifudin Khafid, Muhammad Zaky; Sateria, Angga; Suzen, Zaldy S (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
Technology is evolving, and so is the manufacturing process in the industrial world. One technology that is widely used in making products with ideal dimensions is 3D printing. One of the widely used 3D printing methods is Fused Deposition Modeling (FDM). The working principle of FDM is to extrude thermoplastic filaments through a heated nozzle and print layer by layer. With the development of technology, the filaments used in 3D printing also vary. Carbon Fyber is one of the most popular materials in the industry due to its strength and durability. This study was conducted to find the optimal combination of nozzle temperature, layer height, and print speed parameters for dimensional accuracy and surface roughness on Carbon Fyber filament products. The process parameters used in this study are nozzle temperature, layer height, and print speed. The nozzle temperatures used were 195°C, 210°C, and 225°C. The layer height variations used were 0.15mm, 0.20mm, and 0.25mm. Meanwhile, the print speed is 70%, 85%, and 100%. The parameters will be arranged based on the orthogonal matrix L27(33) with interactions between parameters. Response parameters used are surface roughness and dimensional accuracy. From this study it can be concluded that the parameter that has the most influence on both responses is layer height. Parameter optimization for Carbon Fyber filament products can use the parameters of nozzle temperature 195°C, layer height 0.20mm, and print speed 85%.